Cost-effective interventions to prevent non-communicable diseases: increasing the evidence base in India and other low- and middle-income settings - Eggleston, Karen; Jain, Radhika (BMC medicine, 2020)
[...]in recent years, the government has taken several steps towards establishing the infrastructure for evidence-based priority setting and resource allocation [3], including the establishment of a body for Health Technology Assessment in India (HTAIn) within the Department of Health Research to collate and generate evidence on the clinical efficacy and cost-effectiveness of new and existing health technologies and programs [4]. Levels of several critical risk behaviors, such as alcohol and tobacco use, low physical activity, and unhealthy diet are increasing in socioeconomic status and will require explicit intervention beyond economic development or access to curative care alone. Because the risk factors for chronic diseases are overlapping, the benefits of preventive interventions targeting them are likely to extend beyond preventing diabetes or any other single NCD. [...]the uncertainty analyses suggest that 80% or more of bootstrap estimates were cost-effective and that the ICERs remained below the cost-effectiveness threshold in sensitivity analyses moving the costs and effectiveness up or down by 10–30%. [...]many health conditions could be prevented if all middle-aged individuals adhered to lifestyles with high physical activity, healthy eating habits, no tobacco, limited alcohol, and adequate sleep—the risk factors targeted in K-DPP. [...]health-promoting interventions complement existing policy efforts to support healthy aging [10].